Anticonvulsive Effects and Pharmacokinetic Profile of Cannabidiol (CBD) in the Pentylenetetrazol (PTZ) or N-Methyl-D-Aspartate (NMDA) Models of Seizures in Infantile Rats - Uttl, Libor; Hložek, Tomáš; Mareš, Pavel; Páleníček, Tomáš; Kubová, Hana (International Journal of Molecular Sciences, 2021)
In spite of use of cannabidiol (CBD), a non-psychoactive cannabinoid, in pediatric patients with epilepsy, preclinical studies on its effects in immature animals are very limited. In the present study we investigated anti-seizure activity of CBD (10 and 60 mg/kg administered intraperitoneally) in two models of chemically induced seizures in infantile (12-days old) rats. Seizures were induced either with pentylenetetrazol (PTZ) or N-methyl-D-aspartate (NMDA). In parallel, brain and plasma levels of CBD and possible motor adverse effects were assessed in the righting reflex and the bar holding tests. CBD was ineffective against NMDA-induced seizures, but in a dose 60 mg/kg abolished the tonic phase of PTZ-induced generalized seizures. Plasma and brain levels of CBD were determined up to 24 h after administration. Peak CBD levels in the brain (996 ± 128 and 5689 ± 150 ng/g after the 10- and 60-mg/kg doses, respectively) were reached 1–2 h after administration and were still detectable 24 h later (120 ± 12 and 904 ± 63 ng/g, respectively). None of the doses negatively affected motor performance within 1 h after administration, but CBD in both doses blocked improvement in the bar holding test with repeated exposure to this task. Taken together, anti-seizure activity of CBD in infantile animals is dose and model dependent, and at therapeutic doses CBD does not cause motor impairment. The potential risk of CBD for motor learning seen in repeated motor tests has to be further examined.